KULIAH KERJA NYATA UNIVERSITAS COKROAMINOTO YOGYAKARTA SEBAGAI WUJUD PENGABDIAN MASYARAKAT - Asmarayani, Dwi Vera; Suharyanto, Indra (Universitas Cokroaminoto Yogyakarta, 2024)
Waste management is a separate problem in Yogyakarta. The practice of managing waste from home is to reduce landfill waste, reuse waste, and recycle waste or commonly known as 3R, namely reduce, reuse, recycle. The implementation of waste management from home requires understanding and concern from the community. The waste bank is an alternative for managing household inorganic waste by the community. Waste management through waste banks can improve the people's economy. Management of organic waste at the household level is by processing organic waste into liquid fertilizer using composter media. The main programs and activities of KKN in Pandeyan Village, Pandeyan Village for 45 (forty five) calendar days are focused on inorganic waste management through waste banks and organic waste management using composter media.